Adoption of PICS bags in Northern Nigeria: a case study of Jigawa, Kano, and Katsina States - Abdoulaye, Tahirou; Ayedun, B.; Musa, S.A.; Lowenberg-Deboer, J.; Baributsa, D.; Yakubu, S.A.; Idris, A.A. (International Institute of Tropical Agriculture, 2012)
Cowpea is a key cash crop and also a staple food for millions of people in West and Central Africa. Cowpea trade is severely hampered by storage insects especially the cowpea weevil. The Purdue Improved Cowpea Storage (PICS) project was started in Nigeria in 2008 on a pilot basis in the states of Kano, Katsina, Jigawa, and Plateau. It has since June 2009 been extended to all 19 northern states and the Federal Capital Territory. The PICS project has introduced hermetic storage in triple layer sacks (PICS bags) which have an outer layer of woven polypropylene and two liners of 80 micron high density polyethylene capable of protecting stored cowpeas. The main objective of the PICS is to transfer this technology while helping the establishment of a sustainable supply chain for the production and distribution of PICS bags in Nigeria. IITA and Agricultural Development Programs (ADPs) from those states have conducted public demonstrations in some villages in the pilot states. A survey was conducted in 2009 in Kano, Jigawa, and Katsina states in both demonstration villages and non-demonstration villages. Results indicate a relatively good adoption rate of 21.4% in the general population after just one season of demonstrations in Nigeria. Among farmers who attended village demonstrations, the adoption rate was even higher at 43%; it was even higher for pilot farmers at about 64% of the sample. Based on probit regression results, key factors influencing adoption of PICS bags were found to include: being from a demonstration village (P = 5%), attendance of village demonstration (P = 1%), and other information variables such as being a member of an association (P = 1%), having access to radio messages (P = 1%), and cowpea production (P = 1%). The major problem across the board was that the bag was not readily available in the villages. Therefore, continued development of the supply chain to ensure avaialbility of bags in villages will be essential for the future of this technology in Nigeria.